Compliance with Iron Tablet Consumption and the Risk of Anemia in Third Trimester Pregnant Women in the Context of Midwifery Communication - Yuliwati Yuliwati; Siti Maisaroh (Jurnal Ners, 2026)
Anemia in third trimester pregnant women remains a common health issue and has the potential to increase the risk of pregnancy complications. Iron tablet consumption is one of the preventive measures for anemia, but the level of compliance among pregnant women in consuming them varies, influenced by individual characteristics, knowledge levels, and midwifery communication processes during antenatal care. This study aims to analyze iron tablet consumption compliance and the risk of anemia in third-trimester pregnant women in the context of midwifery communication in the working area of the "J" Community Health Center in 2025. This study used a cross-sectional design. The research subjects were third trimester pregnant women who underwent pregnancy check-ups at the "J" Community Health Center during the period of September–November 2025, with a sample size of 62 respondents. Compliance with iron tablet consumption was determined based on a minimum consumption of 90 tablets during pregnancy, while the incidence of anemia was determined based on hemoglobin levels. Data analysis was performed using univariate and bivariate analysis with the Chi-square test and presented in Odds Ratio (OR) values with a 95% confidence level. The results showed that most pregnant women were non-compliant in consuming iron tablets (67.7%), and anemia was found in 82.3% of respondents. Bivariate analysis showed a significant difference in the risk of anemia between pregnant women who adhered to and did not adhere to iron tablet consumption (p = 0.014). Pregnant women who did not adhere to iron tablet consumption had a higher risk of anemia than pregnant women who adhered to iron tablet consumption (OR = 5.115; 95% CI: 1.286–20.343). Variations in the incidence of anemia were also found based on maternal age (p = 0.015) and level of knowledge (p < 0.001), while parity did not show a significant relationship (p = 0.679). There is a correlation between iron tablet compliance and the risk of anemia in third trimester pregnant women. Iron tablet compliance plays an important role in reducing the risk of anemia, so strengthening midwifery communication through education and assistance during antenatal care needs to be continuously improved as part of efforts to prevent anemia in pregnant women